The development of the first Sudanese grain sorghum hybrids (sorghum bicolor L. Moench) for use under rainfed conditions of Sudan. - Elasha, Elasha Abdelhay (Gezira Journal of Agricultural Science; Vol 19 No 1 (2021), 2023)
Abstract             This experimental work was carried during 2012 and 2014 seasons at three rainfed sites; Suki, Gedarif and Damazin. The hybrids tested were NS -5655, NS-5511 , A8xR2 , A30xR4 , A6xR10 , A41xR8 and HD-1 used as a check. The A8xR2 , A30xR4 , A6xR10 and A41xR8 are local Sudanese hybrids developed by Prof. Elasha A. Elasha at the Sorghum Research Program of the Agricultural Research Corporation (ARC), Sudan. NS -5655, NS-5511 are foreign hybrids introduced from outside and supplied by Mahgoub sons Company . Land was prepared by disc harrowing followed by ridging at the three rain-fed sites. The design at each site and season was a randomized complete block with four replications. Sowing was done at the first week of July and all other cultural practices were carried as recommended by ARC. The agronomic traits measured were days to 50% flowering, panicle length, plant height, grain yield, stover yield and 100 grain weights. Data was analyzed by IRRISTAT (2005) for separate seasons and both combined and stability analyses were carried according to the procedure of Eberhart and Russel ( 1966). The results showed that, t he mean squares of hybrids, environments and hybrids x environments interaction were highly significant (P<0.01) for grain yield. The overall mean grain yield over rainfed environments showed that, hybrids NS-5511 obtained 1.8 t/ha, A6xR10 1.8 t/ha, A30xR4 1.6 t/ha and A8xR2 1.5 t/ha higher than the grain grain yield of HD-1 which was 1.2 t/ha. The results showed that , these hybrids were also more adaptable and stable across the rainfed environments; in addition to their higher grain and stover yields compared to the check HD-1. Also, they were earlier in flowering with suitable plant height.